Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

Solve this system of equations using substitution. Put your answer in ordered pair form, (x, y). x - 2y = -1 2x - y = 4

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

x - 2y = -1 2x - y = 4
Plug in a made up value for one of the variables to figure out what the other would be to make the equation valid. For example, if you set y to equal 1, then x has to equal 1, because 1 minus 2 equals -1.
need help fast

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

if y equaled 2, x would have to equal 5 to satisfy the equations parameters, and those x and y values you achieve are your coordinates.
x=11 , y=6.
11,6 is not the answer
rewrite the first to x = -1+2y and inset in the second 2(-1+2y)-y=4 and solve -2+4y-y = 4 -2+3y=4 3y = 4+2 y = 6/2 y=3 x = -1+2y x=-1+2*3 x = 5
what is the answer?
x = 5, y = 3
5,3 is not the answer
sry 6/3 y = 2 x = 3
rewrite the first to x = -1+2y and inset in the second 2(-1+2y)-y=4 and solve -2+4y-y = 4 -2+3y=4 3y = 4+2 y = 6/3 y=2 x = -1+2y x=-1+2*2 x = 3
x-2y=-1 /2 2x-y=4 2x-4y=-2 2x-y=4 ---------- -- -3y=-6 y=-6/-3= 2 than y=2 --- 2x-2=4 --- 2x=6 --- x=6/2 =3 x=3 y=2

Not the answer you are looking for?

Search for more explanations.

Ask your own question